Inhibition of lung tumorigenesis by a small molecule CA170 targeting the immune checkpoint protein VISTA - Jing Pan (Nature Portfolio, 2021)
Pan, Chen, Zhang et al. investigated the anti-cancer efficacy of CA170, a small molecule agonist of VISTA, on mouse lung tumorigenesis. When combined with a MHCII-directed KRAS peptide vaccine, the authors reported that CA170 suppressed lung tumor development by increasing CD8+ T cell and decreasing MDSC and Treg infiltration, while the Kras vaccine induced CD4+ effector T cell expansion